Introduction: Special Issue on China I - He, Zhiguo; Wang, Yongxiang (Review of Finance, 2022)
China may soon become the world’s largest economy, but most academic research in top journals is based on USA and European data. The insights from these papers with western perspectives may not necessarily apply to China, given its unique set of institutional features. At the same time, many aspects of the Chinese economy are shared by other developing as well as developed countries, such as potential conflicts of interest between majority and minority shareholders, the prevalence of state ownership, and the intricate interactions between market mechanisms and policy interventions. Therefore, the insights from “China” papers, which typically take advantage of unique institutional settings in China, could be of great value to countries far beyond China, independent of whether the research is aimed at certain general economic questions or explores China-specific economic and social issues.